The Effect of Patient Arrival Time on Overall Wait Time and Utilization of Physician and Examination Room Resources in the Outpatient Urology Clinic - Onisuru T. Okotie; Neel Patel; Chris M. Gonzalez (Advances in Urology)
Introduction and objective. We examined patient waiting times, physician utilization, and exam room utilization in order to identify process improvements that may improve patient satisfaction. Methods. Time patient arrived to clinic, time patient was placed in the exam room, time the physician arrived in the exam room, and time physician discharged the patient from the exam room were prospectively recorded for 226 outpatient visits. Results. Overall, 63.2% of patients were on time for their scheduled appointment with 14.8% patient “no-shows.” On-time patients were found to have a longer wait time once in the exam room for the physician than those that were late (14.8±9.2 minutes versus 11.0±8.4 minutes, 𝑃=.005); however, those patients spent a significantly longer time with the physician (10.7±6.0 minutes versus 8.9±5.8 minutes, 𝑃=.041). Exam room utilization was lower for late patients (28.9% versus 44.7%, 𝑃=.03) with physician utilization lower in clinics with 3 or more late patients when compared to clinics with 2 or fewer (59.7% versus 68.7%, 𝑃=.004). Conclusions. Late patients had significantly less time with the physician than on-time patients. Late patients also decreased the overall efficiency of the clinic; therefore, measures to reduce late patients are vital to improve clinic efficiency.